Development and evaluation of an interdisciplinary teaching model via 3D printing - Marcel Reymus; Anja Liebermann; Christian Diegritz; Andreas Keßler (Wiley, 2021)
Abstract The investigation aimed to assess the feasibility of creating an interdisciplinary training model simulating endodontic, restorative as well as implantologic treatment procedures by using 3D printing technology. A CBCT scan of the mandible of a real patient was initially taken. The generated DICOM‐data were converted to a STL‐file, which was further processed to design spaces for exchangeable replica teeth, a bone segment and an adapter to fix the model in a mannequin's head. After the manufacturing process, the model was evaluated by dental students performing a root canal treatment, the insertion of a glass fibre post and the insertion of an implant. The workflow allowed a simple and cost‐effective way of manufacturing a single model, which is suitable for several training scenarios in the fields of endodontics, prosthodontics and implantology. The model was rated as being comparable to the real patient situation and offers repetitive treatment simulations. The present workflow is a feasible way of using DICOM‐data and 3D printing for an interdisciplinary training model. The dental schools can design models according to their own curriculum and put the focus on a patient centered education.